The identification of soil fungi isolated from rhizosphere in different varieties of jali (Coix lacryma-jobi) in Loa Kulu, Kutai Kartanegara, Indonesia (Asian Journal of Agriculture, 2018)
Abstract. Sopialena, Akhsan N, Suryadi A, Nurdiana J. 2018. The identification of soil fungi isolated from Rhizosphere in different varieties of jali plants (Coix lacryma-jobi) in Loa Kulu, Kutai Kartanegara, Indonesia. Asian J Agric 2: 44-47. Rhizosphere effects can indicate the development of an active microbial population around the roots, driving from a loss of organic materials. This research was intended to identify rhizosphere microbes by identifying the potential microbes of four different varieties of jali (Coix lacryma-jobi L.) in Loh Sumber, Loa Kulu, Kutai Kartanegara, Indonesia, i.e., jelai beras, jelai ketan, ketan lekat, and jelai kaltara. The soil samples were collected and isolated in a jali plantation in Loa Kulu, Kutai Kartanegara at 45 days after planting. As many as 16 isolated samples were used, collected from four different varieties of jali and replicated 4 times. The results showed that a variety of microbes at Rhizosphere could be classified as Trichoderma sp., Aspergillus sp., Pythium sp., Fusarium sp., Cunninghamelal sp., and Penicillium sp.